Mind the (knowledge) gap: The effect of a communication instrument on emergency department patients' comprehension of and satisfaction with care. Issue 2 (February 2015) - Simmons, Stefanie; Sharp, Brian; Fowler, Jennifer; Fowkes, Hope; Paz-Arabo, Patricia; Dilt-Skaggs, Mary Kate; Singal, Bonita; Carter, Thomas
Highlights A communication tool was developed through focus groups and a pilot study was performed. The novel tool, the "MyInformer", was then evaluated in four Emergency Department settings. Patient satisfaction with communication and comprehension of care was not affected. Greater comprehension defects were seen in elderly and extremely elderly patients.